Dual-energy computed tomography for prediction of loco-regional recurrence after radiotherapy in larynx and hypopharynx squamous cell carcinoma. Issue 110 (January 2019) - Bahig, Houda; Lapointe, Andréanne; Bedwani, Stéphane; de Guise, Jacques; Lambert, Louise; Filion, Edith; Roberge, David; Létourneau-Guillon, Laurent; Blais, Danis; Ng, Sweet Ping; Nguyen-Tan, Phuc Félix
Abstract: Purpose: To investigate the role of quantitative pre-treatment dual-energy computed tomography (DECT) for prediction of loco-regional recurrence (LRR) in patients with larynx/hypopharynx squamous cell cancer (L/H SCC). Methods: Patients with L/H SCC treated with curative intent loco-regional radiotherapy and that underwent treatment planning with contrast-enhanced DECT of the neck were included. Primary and nodal gross tumor volumes (GTVp and GTVn) were contoured and transferred into a Matlab® workspace. Using a two-material decomposition, GTV iodine concentration (IC) maps were obtained. Quantitative histogram statistics (maximum, mean, standard deviation, kurtosis and skewness) were retrieved from the IC maps. Cox regression analysis was conducted to determine potential predictive factors of LRR. Results: Twenty-five patients, including 20 supraglottic and 5 pyriform sinus tumors were analysed. Stage I, II, III, IVa and IVb constituted 4% (1 patient), 24%, 36%, 28% and 8% of patients, respectively; 44% had concurrent chemo-radiotherapy and 28% had neodjuvant chemotherapy. Median follow-up was 21 months. Locoregional control at 1 and 2 years were 75% and 69%, respectively. For the entire cohort, GTVn volume (HR 1.177 [ 1.001-1.392 ], p = 0.05), voxel-based maximum IC of GTVp (HR 1.099 [95% CI: 1.001–1.209], p = 0.05) and IC standard deviation of GTVn (HR 9.300 [95% CI: 1.113–77.725] p = 0.04) were predictive of LRR. On subgroup analysis of patients treated with upfront radiotherapy +/- chemotherapy, both voxel-based maximum IC of GTVp (HR 1.127 [95% CI: 1.010–1.258], p = 0.05) and IC kurtosis of GTVp (HR 1.088 [95% CI: 1.014–1.166], p = 0.02) were predictive of LRR. Conclusion: This exploratory study suggests that pre-radiotherapy DECT-derived IC quantitative analysis of tumoral volume may help predict LRR in L/H SCC.